2020
DOI: 10.25304/rlt.v28.2368
|View full text |Cite
|
Sign up to set email alerts
|

‘This is two different worlds, you have the asylum world and you have the study world’: an exploration of refugee participation in online Irish higher education

Abstract: This qualitative study explores the transition experiences of refugees to study online in Dublin City University (DCU). Asylum seekers face financial, structural, cultural and digital equity barriers to access higher education (HE). In response to these barriers to access, DCU became a 'University of Sanctuary' in 2017, offering scholarships to refugees. Data were collected via semi-structured interviews. Four themes were constructed in the data-led thematic analysis: asylum world, belonging to the DCU communi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
8
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 24 publications
(27 reference statements)
3
8
0
Order By: Relevance
“…These findings suggest that the students were still able to adapt to online learning and acquire an identity as an online learner, regardless of the barriers, and through participation and regular attendance, they achieved a SoB within a virtual space, giving them a routine and hope for the future. The present data are consistent with previous literature (Crea & McFarland, 2015;Brunton et al, 2019;Farrell et al, 2020).…”
Section: Impact On a Sense Of Belongingsupporting
confidence: 94%
See 4 more Smart Citations
“…These findings suggest that the students were still able to adapt to online learning and acquire an identity as an online learner, regardless of the barriers, and through participation and regular attendance, they achieved a SoB within a virtual space, giving them a routine and hope for the future. The present data are consistent with previous literature (Crea & McFarland, 2015;Brunton et al, 2019;Farrell et al, 2020).…”
Section: Impact On a Sense Of Belongingsupporting
confidence: 94%
“…The classroom was referred to as a supportive environment for refugees; it was an escape from the harsh living conditions. This finding is consistent with Farrell et al (2020), who found that the asylum world and the study world clashed, creating a stressful experience to balance both worlds, especially learning within an environment that generates anxiety, loneliness, stress and depression.…”
Section: Challenges and Impact On Identitysupporting
confidence: 90%
See 3 more Smart Citations